The effect of distributive justice on intention to pay zakat through zakat institutions using affective and cognitive trust as intervening variables - Arsyad Abror; Ataina Hudayati (Jurnal Ekonomi & Keuangan Islam, 2020)
The purpose of this study was to examine the effect of distributive justice on the intention to pay zakat through Zakat Institutions (ZIs), using affective trust and cognitive trust as intervening variables. Data collection techniques through the distribution of questionnaires to 272 Muslims in Yogyakarta. Data analysis using Structural Equation Modeling (SEM) with SmartPLS software version 3.2. The findings show that the distributive justice has a positive effect on intention to pay zakat through ZIs, as well as has a positive effect on affective and cognitive trust. In addition, affective and cognitive trust has a positive effect on intention to pay zakat through ZIs. The results of the study also show that affective and cognitive trust are intervening variables on the relationship between distributive justice and the intention to pay zakat through ZIs.